City of scoundrels ebook The 12 days of disaster that gave birth to modern chicago. - Krist, Gary (2012)
The masterfully told story of twelve volatile days in the life of Chicago, when an aviation disaster, a race riot, a crippling transit strike, and a sensational child murder transfixed and roiled a city already on the brink of collapse. When 1919 began, the city of Chicago seemed on the verge of transformation. Modernizers had an audacious, expensive plan to turn the city from a brawling, unglamorous place into "the Metropolis of the World." But just as the dream seemed within reach, pandemonium broke loose and the city's highest ambitions were suddenly under attack by the same unbridled energies that had given birth to them in the first place. It began on a balmy Monday afternoon when a blimp in flames crashed through the roof of a busy downtown bank, incinerating those inside. Within days, a racial incident at a hot, crowded South Side beach spiraled into one of the worst urban riots in American history, followed by a transit strike that paralyzed the city. Then, when it seemed as if things could get no worse, police searching for a six-year-old girl discovered her body in a dark North Side basement. Meticulously researched and expertly paced, City of Scoundrels captures the tumultuous birth of the modern American city, with all of its light and dark aspects in vivid relief.